The importance of teaching English reading in foundation phase in primary schools: Case study in Maune Circuit, Capricorn North District, Limpopo province - Rhoda, Mojapelo Mmasefudi; Phindane, Pule; Ngobeni, Elias Tsakane; Phage, Itumeleng (Research in English Language Teaching, 2024)
Reading ability is important in education as it transcends all forms of learning. Poor reading ability leads academic challenges and poor performance in school. In the South African school curriculum, most subjects are taught in the second language, which is mainly English; therefore, learning to read English early in formal schooling years forms the foundation for successful learning. The purpose of this study was to understand the importance of teaching English reading in Foundation Phase (FP) in primary schools of Maune Circuit Capricorn North District Limpopo Province. The study employed an interpretive paradigm with a qualitative approach. Data was collected from ten FP teachers from three primary schools in Maune Circuit, using semi-structured interviews. Thematic analysis was used to identify categories, subcategories, and themes to interpret the findings. Findings revealed that English language is valued in South African society even though it is only a subject English First Additional Language (EFAL) in FP. Learners are challenged in English reading due to limited exposed to English at home; the mother tongue is spoken at home, and only encounter English reading in the classroom. Learners are experiencing language confusion because they are learning to read in their mother tongue as the Language of Learning and Teaching (LoLT) and English as a subject. This negatively affects other subjects; however, English reading is important in FP as it prepares learners for English as LoLT from Grade 4. It is a prerequisite that learners should acquire adequate foundational skills in English reading in FP.